Notes on Norwegian marine Amphipoda 7. Amphipod associates of Geodia sponges in western Norway - Wim Vader (Fauna Norvegica, 1984)
The rarely collected amphipod species Amphithopsis longicaudata Boeck (Calliopiidae), Cheirimedon latimanus (Sars) (Lysianassidae), Laothoes meinerti Boeck (Calliopiidae) and Phippsiella similis (Sars) (Stegocephalidae) have been collected in the Bergen area, western Norway, in association with the large and compact sponges of the genus Geodia. The amphipods seem to live on rather than in the sponge hosts.